2022
DOI: 10.1007/s40265-022-01731-1
|View full text |Cite
|
Sign up to set email alerts
|

Tixagevimab + Cilgavimab: First Approval

Abstract: Tixagevimab 150 mg and cilgavimab 150 mg (EVUSHELD TM 150 mg + 150 mg solution for injection; tixagevimab + cilgavimab) is an intramuscular (IM) long-acting monoclonal antibody combination developed by AstraZeneca for the prevention and treatment of COVID-19. In March 2022, tixagevimab + cilgavimab was approved in the UK for pre-exposure prophylaxis of COVID-19 in adults who are not currently infected with SARS-CoV-2 and who have not had a known recent exposure to an individual infected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
29
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 19 publications
1
29
0
1
Order By: Relevance
“…In addition, one study data from the AstraZeneca showed a protective effect against symptomatic COVID-19 infection in RT-PCR-negative patients treated with tixagevimab/cilgavimab compared with placebo-treated control recipients (RR 73%; 95% CI 27-90), which is also consistent with our findings 2 .Furthermore, it deserves our attention that several studies conclusions were drawn in settings where the major proportion of omicron mutations was present. In the context of the reduced neutralizing activity of several Monoclonal antibodies due to the omicron mutations, tixagevimab-cilgavimab may still serve as an effective and targeted therapeutic strategy 1 .…”
supporting
confidence: 90%
See 1 more Smart Citation
“…In addition, one study data from the AstraZeneca showed a protective effect against symptomatic COVID-19 infection in RT-PCR-negative patients treated with tixagevimab/cilgavimab compared with placebo-treated control recipients (RR 73%; 95% CI 27-90), which is also consistent with our findings 2 .Furthermore, it deserves our attention that several studies conclusions were drawn in settings where the major proportion of omicron mutations was present. In the context of the reduced neutralizing activity of several Monoclonal antibodies due to the omicron mutations, tixagevimab-cilgavimab may still serve as an effective and targeted therapeutic strategy 1 .…”
supporting
confidence: 90%
“…Tixagevimab-cilgavimab is one type of long-acting monoclonal antibody combination produced from B cells donated by patients recovered from COVID-19,which is given via intramuscular injection to prevent and treat COVID-19. Tixagevimab-cilgavimab can bind to several different sites on the SARS-CoV-2 spike protein and may help overcome immune escape and maintain susceptibility to SARS-CoV-2 variants 2 .…”
mentioning
confidence: 99%
“…It is effective against both SARS-CoV and SARS-CoV2, as it recognizes the common epitopes in both the RBDs. The combination of anti-RBD mAbs, tixagevimab (AZD8895)/cilgavimab (AZD1061), also received emergency approval from FDA [ 18 ]. As the pandemic went on, new variants emerged [ [19] , [20] , [21] , [22] ].…”
Section: Introductionmentioning
confidence: 99%
“…The recommended dose is 300 mg, consisting of 150 mg of tixagevimab and 150 mg of cilgavimab administered as separate sequential intramuscular (IM) injections at different injection sites in two different muscles, preferably in the gluteal muscles. A higher 600 mg dose, consisting of 300 mg of tixagevimab and 300 mg of cilgavimab, may be more appropriate for some SARS-CoV-2 variants [ 63 ].…”
Section: Biological Agentsmentioning
confidence: 99%